2016
DOI: 10.1590/2317-1782/20162015238
|View full text |Cite
|
Sign up to set email alerts
|

Autoavaliação da comunicação em promotores de justiça em um estado do nordeste, Brasil

Abstract: RESUMO Objetivo Descrever a autoavaliação do promotor de justiça quanto à sua comunicação e reação do ouvinte e analisar a relação com o gênero, idade e anos de trabalho. Método Desenho descritivo, transversal. Foi elaborado um questionário e enviado aos 126 promotores, sendo devolvidos 33 questionários preenchidos. As variáveis independentes foram o gênero, idade e anos do exercício profissional. As variáveis dependentes foram a autoavaliação da comunicação ao longo dos anos de trabalho, os parâmetros de co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…As in the result of the present study was not statistically significant between the gender, but it can be observed that women tended to have a greater negative impact than men. Public speaking seems to be more challenging for women, they feel insecure and tense, probably because they perceive more negative elements during communication 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…As in the result of the present study was not statistically significant between the gender, but it can be observed that women tended to have a greater negative impact than men. Public speaking seems to be more challenging for women, they feel insecure and tense, probably because they perceive more negative elements during communication 14,15 .…”
Section: Discussionmentioning
confidence: 99%